An ethnographic study on managing diversity in two Protestant theological colleges - Naidoo, Marilyn ca. 20./21. Jh. (HTS teologiese studies, 2016)
For many reasons Christian higher education institutions struggle to embrace diversity. Diversity is a relationship of mutuality, where differences are engaged and respected. This study aimed to understand diversity management via the institutional culture to understand how these interactions of dealing with diversity form and prepare future religious leaders. These issues are highlighted through two case studies conducted in the main-line Protestant tradition. Diversity was represented in issues of race, ethnicity, class, gender and sexual orientation, which have an interlocking nature. Findings suggest a colour-blind theology in one institution, perpetuating surface change, and a lack of structure, alignment and capacity in diversity in the other institution. In both institutions diversity was not linked positively to ministerial identity formation to make a significant difference. This study highlights the lack of consciousness of the way in which institutions are organised, which then holds direct consequences for students, identity and transformation.